The effects of carbon ion implantation on wettability, abrasion, thermal and anti-corrosion stabilities of laser ablated super-hydrophobic Nitinol surface - Meng Wang; Chengjuan Yang; Zhen Yang; Yanling Tian (Journal of Materials Research and Technology, 2024)
Comparing with pure laser irradiation, the hybrid fabrication using laser ablation and chemical modification is one of the widely used techniques to obtain bio-inspired super-hydrophobic surface. Nevertheless, conventional surface chemical modification techniques have faced challenges including the detachment of micro-nano structures and the instability of super-hydrophobic surfaces. This research introduces an innovative method for creating extremely stable super-hydrophobic surfaces on NiTi alloy through a combination of laser exposure, carbon ion implantation, and modification with fluoroalkylsilane (FAS). Surface morphology and chemical component were systematically investigated to reveal the formation mechanism of super-hydrophobicity. Besides, its abrasion stability, thermal stability and corrosion resistance stability of this kind of super-hydrophobic surface were also investigated. And the corresponding stability improvement mechanisms were further revealed.